2012
DOI: 10.1016/j.cognition.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping in a language of thought: A formal model of numerical concept learning

Abstract: In acquiring number words, children exhibit a qualitative leap in which they transition from understanding a few number words, to possessing a recursive system of interrelated numerical concepts. We present a computational framework for understanding this inductive leap as the consequence of statistical inference over a sufficiently powerful representational system. We provide an implemented model that is powerful enough to learn number word meanings and other related conceptual systems from naturalistic data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
173
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(183 citation statements)
references
References 52 publications
(63 reference statements)
4
173
1
1
Order By: Relevance
“…Specifically, on the assumption that delays between subset knower level stages are driven by the problem of mapping numerals to set sizes, it remains unknown why this 6 Consistent with this, computational models of the counting stages suggest that, to the extent that learning the cardinal principle is a process of inference to the best explanation where the successor principle is contained in a child's initial hypothesis space, children may indeed skip steps given sufficient robust training with, e.g., one and two, but not three or four (Piantadosi, et al, 2012). mapping problem might be so difficult.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, on the assumption that delays between subset knower level stages are driven by the problem of mapping numerals to set sizes, it remains unknown why this 6 Consistent with this, computational models of the counting stages suggest that, to the extent that learning the cardinal principle is a process of inference to the best explanation where the successor principle is contained in a child's initial hypothesis space, children may indeed skip steps given sufficient robust training with, e.g., one and two, but not three or four (Piantadosi, et al, 2012). mapping problem might be so difficult.…”
Section: Discussionmentioning
confidence: 94%
“…Also, the stage-like nature of children's learning has been corroborated by meta-analyses and computational models (Lee & Sarnecka, 2010Sarnecka & Lee, 2009), which can model the delays between stages using a small number of parameters (Piantadosi, et al, 2012).…”
Section: Bilingual Number Word Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some previous studies, children have knowledge of the successor function early in childhood -either innately (Leslie, Gallistel, & Gelman, 2007) or when they become Cardinal Principle knowers (CPknowers) at around 3½ to 4 years of age (Carey, 2004(Carey, , 2009Piantadosi, Tenenbaum, & Goodman, 2012;Sarnecka & Carey, 2008). Other studies have suggested that this knowledge emerges sometime after children learn the cardinal principle (Davidson, Eng, & Barner, 2012), providing evidence that children only have item-based knowledge of the successor function when they become CP-knowers (see also Wagner, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant view in developmental psychology as reviewed by Rips et al (2008), however, is that the natural number system is constructed out of other number-related concepts in the course of children's cognitive development (see Carey 2009;Feigenson et al 2004;Le Corre et al 2006;Piantadosi et al 2012;Sarnecka to appear;and Wynn 1992, among many others). The major difficulty for the nativist position is the fact that acquisition of number words (or numerals) by children takes a long time, completed only at the age of three and a half to four years.…”
Section: Introductionmentioning
confidence: 99%